Comparative Transcriptome Analysis of Artificially Induced Rough-Mutant Brucella Strain RM57 and Its Parent Strain Brucella melitensis M1981 - Peng, Xiaowei; Liu, Yufu; Qin, Yuming; Jiang, Hui; Feng, Yu; Sun, Jiali; Niu, Kai; Gao, Qiang; Dong, Hao; Ding, Jiabo (Frontiers in Veterinary Science, 2020)
Brucellosis is one of the most common zoonotic epidemics with a serious threat to public health and livestock development in many countries across the world. Vaccination is a key control strategy toward preventing brucellosis in high-prevalence regions. Recently, a rough-type Brucella melitensis mutant strain (RM57) induced from a B. melitensis strain M1981 showed protective effects in guinea pigs indicating that it is a good vaccine candidate. In this study, stress response assays were performed to reveal the mechanisms underlying virulence attenuation of RM57. In addition, a genome-wide transcriptome profile of RM57 was analyzed relative to the parent strain M1981 in order to reveal genetic factors controlling the phenotypes. Our results indicated a similar sensitivity to various stress conditions in RM57 owing to a lack of significant differences from its parent strain. Transcriptome analysis showed that a total of 1,205 genes were differentially expressed between RM57 and M1981 with gene ontology terms revealing that these genes are involved in energy production and conversion, translation, ribosomal structure, and biogenesis. Pathway enrichment analysis revealed that genes involved in oxidative phosphorylation, ribosome, nitrogen metabolism, tyrosine metabolism, and two-component system were significantly affected. As a result of these differences at the molecular level, the function of type IV secretion system in RM57 was found to be affected leading to reduced virulence of the RM57 mutant strain in both macrophage and mice infection models.